TOPONOMY IN THE CONSTRUCTION OF CULTURAL IDENTITY OF THE SOUTH MINAHASA COMMUNITY: AN ANTHROPOLINGUISTIC PERSPECTIVE - Vivi Nansy Tumuju; Vany Kamu; Jultje Rattu; Zulfa (LLDIKTI Wilayah X, 2025)
The naming of a region (toponymy) is not merely a geographical label, but rather a linguistic artifact that stores the collective memory and cultural identity of its people. This study aims to dissect the construction of the cultural identity of the South Minahasa community through the meaning of village names from an anthropolinguistic perspective. Using a descriptive qualitative method with an ethnosemantic approach, data were collected through historical document studies, field observations, and in-depth interviews with traditional leaders (Tona'as). The results of the study indicate that the toponymy in South Minahasa consists of 8 villages, namely: Menara city, Maliku and Maliku 1, Ritey, Malanos Baru, Lopana and Lopana 1, Pinalin, Pondang, and Ranomea. These 8 toponyms fall into four main categories: (1) flora and fauna aspects (bioglyphs), (2) geographical aspects (geoglyphs), (3) historical events, and (4) hopes or theological values. The identity construction found represents the deep attachment of the Tou Minahasa community to nature (cosmology) and the spirit of ancestral heroism. The implications of this research emphasize that preserving toponymic meaning is a crucial strategy for maintaining the vitality of local culture amidst the tide of modernization.